Smoking and the risk of breast cancer in BRCA1 and BRCA2 carriers: an update - Ginsburg, Ophira (2008)
Among women with a mutation in BRCA1 or BRCA2, the risk of breast cancer is high, but it may be modified by exogenous and endogenous factors. There is concern that exposure to carcinogens in cigarette smoke may increase the risk of cancer in mutation carriers. We conducted a matched case–control study of 2,538 cases of breast cancer among women with a BRCA1 (n = 1,920) or a BRCA2 (n = 618) mutation. One non-affected mutation carrier control was selected for each case, matched on mutation, country of birth, and year of birth. Odds ratios were calculated using conditional logistic regression, adjusted for oral contraceptive use and parity. Ever-smoking was not associated with an increased breast cancer risk among BRCA1 carriers (OR = 1.09; 95% CI 0.95–1.24) or among BRCA2 carriers (OR = 0.81; 95% CI 0.63–1.05). The result did not differ when cases were restricted to women who completed the questionnaire within two years of diagnosis. A modest, but significant increase in risk was seen among BRCA1 carriers with a past history of smoking (OR = 1.27; 95% CI 1.06–1.50), but not among current smokers (OR = 0.95; 0.81–1.12). There appears to be no increase in the risk of breast cancer associated with current smoking in BRCA1 or BRCA2 carriers. There is a possibility of an increased risk of breast cancer among BRCA1 carriers associated with past smoking. There may be different effects of carcinogens in BRCA mutation carriers, depending upon the timing of exposure.